Стратегія просування виставкових послуг українських компаній на міжнародних ринках - Швець Людмила Андріївна (My University, 2023)
Об’єктом дослідження виступає ринкова діяльність українських компаній на міжнародних ринках. Предметом дослідження є теоретичні та практичні аспекти розробки стратегії просування українських компаній на міжнародному ринку виставкових послуг. Мета дипломної роботи полягає в узагальненні теоретичних положень та розробка практичних рекомендацій щодо просування виставкових послуг українських компаній на міжнародних ринках задля підвищення ефективності їхньої діяльності. За результатами дослідження сформульовані рекомендації щодо побудови стратегії просування виставкових послуг на польському ринку . Отримані результати та висновки можуть бути використані українськими компаніями ,що надають виставкові послуги для організації діяльності на ринку Польщі.

The object of the research is the market activity of Ukrainian companies on international markets. The subject of the research is the theoretical and practical aspects of developing a strategy for the promotion of Ukrainian companies on the international market of exhibition services. The aim of the research is is to generalize the theoretical provisions and develop practical recommendations for the promotion of exhibition services of Ukrainian companies on international markets in order to increase the efficiency of their activities. The practical significance of the research is Based on the results of the research, recommendations were formulated for building a strategy for the promotion of exhibition services on the Polish market. The obtained results and conclusions can be used by Ukrainian companies that provide exhibition services to organize activities on the Polish market.
Promotion strategy for Ukrainian trade fair services companies in international markets